KESIAPAN DOSEN DAN TENAGA PENDIDIK DALAM MENJALANKAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA PADA FAKULTAS BISNIS UNIVERSITAS MEGA BUANA PALOPO - Arianto Dangkeng; Suwandi N Suwandi N; Dewi Hastuty (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
The Merdeka Campus is one of the policies of the Minister of Education and Culture Nadiem Makarim who gave a university policy to give the right to study for three semesters outside the study program. This study aims to measure the readiness of lecturers and education staff in implementing the Merdeka Learning program in the Merdeka Campus within the scope of the Faculty of Business, Mega Buana Palopo University. The research targets are lecturers and education staff, totaling 20 respondents with a total sampling technique. The research method used in this study is to conduct an analytical survey through the distribution of questionnaires to obtain an overview of the readiness of lecturers and education staff regarding the implementation of the MBKM program. The results of this study serve as consideration for those under the Faculty of Business to implement the MBKM program to support the achievement of the vision and mission of the Faculty of Business.